PENINGKATAN KEMAMPUAN MENULIS NARASI BERBASIS KEARIFAN LOKAL PADA SISWA KELAS XI SMAN 18 BONE - Asrianto; Andi Srimularahmah; Muhammad Idris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve narrative writing skills based on local wisdom among the students of Class XI MIPA 2 at SMA Negeri 18 Bone. This research was conducted through Classroom Action Research (CAR) implemented in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The research subjects were 34 students whose initial narrative writing ability was relatively low. The pre-cycle observation revealed that most students had difficulties in organizing narrative structures, developing a coherent plot, and integrating elements of local wisdom—such as customs, cultural values, and Bone folklore—into their writing. To address these challenges, a local wisdom-based learning strategy was applied by utilizing regional folklore texts, cultural discussions, and contextual narrative examples relevant to students’ daily lives. The findings indicated improvement in students’ writing ability in each cycle. In the first cycle, the average score reached 77.35 with a classical mastery level of 94.11%. However, weaknesses were still found in developing conflicts and story depth. Improvements were made in the second cycle through collaborative guidance, richer examples, and direct assistance during the revision process. The results showed a significant increase with an average score of 87.94 and 100% classical mastery. Improvements occurred in all assessment aspects, including narrative structure, plot coherence, language style, and the use of local wisdom elements. Thus, the implementation of local wisdom-based narrative writing proved effective in enhancing students’ writing ability while fostering motivation, creativity, and appreciation for regional culture.